Analisis Pengaruh Pendidikan, Kesehatan Masyarakat, dan Pendapatan per Kapita terhadap Indeks Pembangunan Manusia di Kabupaten Sumbawa Barat - Gina Harlina (Global Leadership Organizational Research in Management, 2024)
This study aims to investigate the influence of education, health, and per capita income towards the Human Development Index in West Sumbawa Regency. The independent variables in this study are education, with the average length of schooling as the indicator, health, with life expectancy as the indicator, and per capita income. The dependent variable is the Human Development Index. The data for these variables are time-series data from 2006 to 2022, obtained directly from the Central Statistics Agency of West Sumbawa Regency. The results of the partial t-test for education and per capita income variables conclude that both education and per capita income have a significant partial effect on the Human Development Index, while the health variable does not have a partial effect. For simultaneous effects, the education, health, and per capita income variables together have an impact on the Human Development Index in West Sumbawa Regency.